PEMBUATAN DAN PENGGUNAAN CAIRAN PEMBERSIH TANGAN (HANDSANITISER) DENGAN BAHAN TAMBAHAN ALOEVERA DI DESA KALISORO KECAMATAN TAWANGMANGU KABUPATEN KARANGANYAR - Hanugrah Ardya Crisdian; Oktavina Permatasari (Abdimas Siliwangi, 2021)
To improve the public health status with the Covid19 pandemic that has spread in almost all parts of the world, for this reason, the community needs training activities for making hand sanitisers and their use in improving community health status in Kalisoro Village, Tawangmangu District, Karanganyar Regency. This community service activity is designed by making and using hand sanitizer / handsanitiser liquid with Aloe vera additives. The target of this activity is that the people of Kalisoro village will get additional knowledge / skills for making handsanitisers and can get the benefits and benefits of the barrier to improve the health status of the community.